2021
DOI: 10.3390/nu13082859
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Protective Effect of Phytate in Bone Decalcification Related-Diseases

Abstract: Myo-inositol hexaphosphate (phytate; IP6) is a natural compound that is abundant in cereals, legumes, and nuts, and it can bind to crystal surfaces and disturb crystal development, acting as crystallization inhibitor. The adsorption of such inhibitors to crystal faces can also inhibit crystal dissolution. The binding of phytate to metal cofactors suggests that it could be used for treatment of osteoporosis. Our in-vitro study showed that phytate inhibits dissolution of hydroxyapatite (HAP). The effect of phyta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…In another study in postmenopausal women, the 10-year fracture probability in the low-phytate group was significantly higher than in the high-phytate group, both in major osteoporotic and hip fracture [ 18 ]. Phytate, in an in vitro study, inhibited hydroxyapatite (HAP) dissolution in a concentration-dependent manner by adsorbing phytate in HAP sur-faces, and this effect was comparable to alendronate but greater than that of etidronate [ 22 ]. Moreover, it has been shown that phytate inhibits osteoclastogenesis in human primary osteoclast cell line and in RAW 264.7 monocyte/macrophage mouse cell line [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In another study in postmenopausal women, the 10-year fracture probability in the low-phytate group was significantly higher than in the high-phytate group, both in major osteoporotic and hip fracture [ 18 ]. Phytate, in an in vitro study, inhibited hydroxyapatite (HAP) dissolution in a concentration-dependent manner by adsorbing phytate in HAP sur-faces, and this effect was comparable to alendronate but greater than that of etidronate [ 22 ]. Moreover, it has been shown that phytate inhibits osteoclastogenesis in human primary osteoclast cell line and in RAW 264.7 monocyte/macrophage mouse cell line [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no negative effects on mineral status have been observed in mineral balanced diets (as Mediterranean diet) with adequate amounts of phytate (0.5–1 g/day) [ 26 , 57 , 58 , 59 , 60 ]. Furthermore, a recent paper has indicated that a phytate consumption higher than 307 mg/day was associated with a normal lumbar BMD (t-score > −1) in postmenopausal women [ 22 ]. Consequently, a healthy and balanced diet with the right amounts of these trace minerals may prevent the loss of bone mass and prevent trace metals deficiencies [ 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their antinutrient activity, phytates might be antioxidants chelating excess iron, thereby avoiding the damaging Fenton reactions ( 46 , 47 ). Phytate could have pleiotropic effect [enhancing immunity, inhibiting inflammatory cascade, decreasing cell proliferation ( 44 , 47 ), decreasing kidney stone risk ( 48 ), osteoporosis risk ( 25 , 49 ), dental calculi ( 50 ), preventing age-related cardiovascular calcification ( 51 , 52 )]. However, these observations need to be confirmed by further research.…”
Section: Relevant Phytochemicals In Cereals and Their Effect On Healthmentioning
confidence: 99%